(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the anemia status of patients with gastrointestinal cancer after surgery at the Oncology Center of Thai Nguyen National Hospital and analyze some related factors. Subjects and methods: A cross-sectional study on 51 subjects with gastrointestinal cancer who underwent surgery at the Oncology Center of Thai Nguyen National Hospital from March 2022 to March 2023. Results: Anemia status was evaluated based on the hemoglobin indicator. The study results showed the overall anemia rate after surgery among the study subjects was 72.5%, with anemia in male patients (59.5%) being higher than in female patients (40.5%), mostly in patients aged 60 and above (78.4%) and belonging to the stomach cancer group (40.6%) and colon cancer group (43.2%). A statistically significant correlation was found between nutritional status, reduced food intake, anorexia, and anemia status in the study subjects (p < 0.05).